Quantizing the Sixties: The Application of Quantum Principles as an Alternative SocioCultural Study of the 1960s American Counterculture - Nebeg ,Leila; Mihoubi ,Ahmed (University of Ammar Theledji -Laghouat, 2021)
In recent years, Quantum Social Science has become the new trending notion for many physicists and social science theorists. The present study attempts to take part in the revolutionizing concept by quantizing the main socio-cultural structures that led to the rise of the 1960s American Counterculture. The reason behind the recent demand for the alternative notion is due to the limitations of the existing sociological theories like the Symbolic Interactionsim and the Conflict Theory which seem to exhibit one-dimensional explanations that are seen as outdated and restricting. Consequently, this research attempted to employ the principles of quantum mechanics, Wave/Particle Duality, Superposition and Entanglement, to capture the multiple perspectives of the counterculture in a holistic and accurate manner. It strived to answer the research questions by constructing a theoretical analysis that detailed the most influential aspects of the counterculture. The present study applied the descriptive analytical method and used the qualitative approach to analyze the 1960s decade as a case study. By assimilating quantum principles, this dissertation made an attempt to offer better, more accurate analysis than those of classical sociological theories in regard to analyzing the structures that led to the popularity of the dynamic decade. Due to the complex, nonlinear nature of both systems, the study sought to parallel the socio-cultural system of the counterculture with the microscopic system of quantum mechanics; thus creating alternative approaches that offer nonrestrictive interpretations of structures like the duality of social movements and individual freedom, the superposition of hippies and activists, the entanglement of the collective groups of race and gender and the issue of the generation gap. This research is an endeavor to further expand the multidisciplinary area of research to the terrain of sociology and socio-cultural studies